GASTRONOMI KOMODITAS PANGAN LOKAL BERBASIS COMMUNITY-BASED TOURISM DAN DAMPAKNYA ATAS TERBENTUKNYA PERAN GANDA PROFESI DI PASAR PAPRINGAN - Indramurti, Meidian Farah; Bagas Narendra Parahita; Yosafat Hermawan Trinugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Local potential cannot be maximized without collaboration within the community based on community based Tourism this is in line with this research. This is in line with the objectives of this research, which are: (1) To identify the process of gastronomy development based on local food commodities at Papringan tourist market; (2) To explain the factors influencing the participation in dual professional roles among traders at Papringan tourist market; (3) To analyze the relationship between dual professional roles and the development of gastronomy based on local food commodities through Community-Based Tourism at Papringan Tourist Market. This research is a collective case study using a collective case study approach. The data sources for this research include observations, field notes, and interviews, while secondary data sources are obtained from government reports, statistical data, books, and journals. The sampling technique used is purposive sampling. Data collection is conducted through observation, interviews, literature review, and documentation. The data validity test technique used is data triangulation, and the data analysis technique employed is narrative analysis. The results of this research are as follows: First, the history, condition, and development of Papringan Market in the culinary. Second, the enthusiasm of the community in the development of Papringan Market is evident from the participation of local residents, traders, and tourists. Third, the dual professional roles of traders at Papringan Market represent a diversity of professions where trading is a secondary job to their primary occupation. Fourth, The formation of traditional culinary gastronomy and development of gastronomy at Papringan Market of harvest products.